Active and fast charge-state switching of single NV centres in diamond by in-plane Al-Schottky junctions - Schreyvogel, Christoph; Polyakov, Vladimir; Burk, Sina; Fedder, Helmut; Denisenko, Andrej; Fávaro de Oliveira, Felipe; Wunderlich, Ralf; Meijer, Jan; Zuerbig, Verena; Wrachtrup, Jörg; Nebel, Christoph E. (Beilstein Journal of Nanotechnology, 2016)
In this paper, we demonstrate an active and fast control of the charge state and hence of the optical and electronic properties of single and near-surface nitrogen-vacancy centres (NV centres) in diamond. This active manipulation is achieved by using a two-dimensional Schottky-diode structure from diamond, i.e., by using aluminium as Schottky contact on a hydrogen terminated diamond surface. By changing the applied potential on the Schottky contact, we are able to actively switch single NV centres between all three charge states NV+, NV0 and NV− on a timescale of 10 to 100 ns, corresponding to a switching frequency of 10–100 MHz. This switching frequency is much higher than the hyperfine interaction frequency between an electron spin (of NV−) and a nuclear spin (of 15N or 13C for example) of 2.66 kHz. This high-frequency charge state switching with a planar diode structure would open the door for many quantum optical applications such as a quantum computer with single NVs for quantum information processing as well as single 13C atoms for long-lifetime storage of quantum information. Furthermore, a control of spectral emission properties of single NVs as a single photon emitters – embedded in photonic structures for example – can be realized which would be vital for quantum communication and cryptography.
Keywords: active charge state control; diamond; fast charge state switching; NV centre; two-dimensional Schottky diode

(untitled) - Kurtsiefer, C.; Mayer, S.; Zarda, P.; Weinfurter, H. (Phys. Rev. Lett., 2000)

(untitled) - Jelezko, F.; Wrachtrup, J. (J. Phys.: Condens. Matter, 2004)

(untitled) - Jelezko, F.; Wrachtrup, J. (Phys. Status Solidi A, 2006)

(untitled) - Maze, J. R.; Stanwix, P. L.; Hodges, J. S.; Hong, S.; Taylor, J. M.; Cappellaro, P.; Jiang, L.; Dutt, M. V. G.; Togan, E.; Zibrov, A. S.; Yacoby, A.; Walsworth, R. L.; et al. (Nature, 2008)

(untitled) - Vaijayanthimala, V.; Chang, H.-C. (Nanomedicine (London, U. K.), 2009)

(untitled) - Gisin, N.; Ribordy, G.; Tittel, W.; Zbinden, H. (Rev. Mod. Phys., 2002)

(untitled) - Beveratos, A.; Brouri, R.; Gacoin, T.; Villing, A.; Poizat, J.-P.; Grangier, P. (Phys. Rev. Lett., 2002)

(untitled) - Rondin, L.; Dantelle, G.; Slablab, A.; Grosshans, F.; Treussart, F.; Bergonzo, P.; Perruchas, S.; Gacoin, T.; Chaigneau, M.; Chang, H.-C.; Jacques, V.; Roch, J.-F. (Phys. Rev. B: Condens. Matter Mater. Phys., 2010)

(untitled) - Fu, K.-M. C.; Santori, C.; Barclay, P. E.; Beausoleil, R. G. (Appl. Phys. Lett., 2010)

(untitled) - Hauf, M. V.; Grotz, B.; Naydenov, B.; Dankerl, M.; Pezzagna, S.; Meijer, J.; Jelezko, F.; Wrachtrup, J.; Stutzmann, M.; Reinhard, F.; Garrido, J. A. (Phys. Rev. B: Condens. Matter Mater. Phys., 2011)

(untitled) - Maurer, P. C.; Kucsko, G.; Latta, C.; Jiang, L.; Yao, N. Y.; Bennett, S. D.; Pastawski, F.; Hunger, D.; Chisholm, N.; Markham, M.; Twitchen, D. J.; Cirac, J. I.; et al. (Science, 2012)

(untitled) - Dolde, F.; Bergholm, V.; Wang, Y.; Jakobi, I.; Naydenov, B.; Pezzagna, S.; Meijer, J.; Jelezko, F.; Neumann, P.; Schulte-Herbrüggen, T.; Biamonte, J.; Wrachtrup, J. (Nat. Commun., 2014)

(untitled) - Doi, Y.; Makino, T.; Kato, H.; Takeuchi, D.; Ogura, M.; Okushi, H.; Morishita, H.; Tashima, T.; Miwa, S.; Yamasaki, S.; Neumann, P.; Wrachtrup, J.; et al. (Phys. Rev. X, 2014)

(untitled) - Cui, S.; Hu, E. L. (Appl. Phys. Lett., 2013)

(untitled) - Grotz, B.; Hauf, M. V.; Dankerl, M.; Naydenov, B.; Pezzagna, S.; Meijer, J.; Jelezko, F.; Wrachtrup, J.; Stutzmann, M.; Reinhard, F.; Garrido, J. A. (Nat. Commun., 2012)

(untitled) - Kato, H.; Wolfer, M.; Schreyvogel, C.; Kunzer, M.; Müller-Sebert, W.; Obloh, H.; Yamasaki, S.; Nebel, C. (Appl. Phys. Lett., 2013)

(untitled) - Hauf, M. V.; Simon, P.; Aslam, N.; Pfender, M.; Neumann, P.; Pezzagna, S.; Meijer, J.; Wrachtrup, J.; Stutzmann, M.; Reinhard, F.; Garrido, J. A. (Nano Lett., 2014)

(untitled) - Nebel, C. E.; Rezek, B.; Shin, D.; Watanabe, H. (Phys. Status Solidi A, 2006)

(untitled) - Garrido, J. A.; Nebel, C. E.; Stutzmann, M.; Snidero, E.; Bergonzo, P. (Appl. Phys. Lett., 2002)

(untitled) - Schreyvogel, C.; Wolfer, M.; Kato, H.; Schreck, M.; Nebel, C. E. (Sci. Rep., 2014)

(untitled) - Schreyvogel, C.; Polyakov, V.; Wunderlich, R.; Meijer, J.; Nebel, C. E. (Sci. Rep., 2015)

(untitled) - Füner, M.; Wild, C.; Koidl, P. (Appl. Phys. Lett., 1998)

(untitled) - Thomas, E. L. H.; Nelson, G. W.; Mandal, S.; Foord, J. S.; Williams, O. A. (Carbon, 2014)

(untitled) - Ziegler, J. F.; Ziegler, M. D.; Biersack, J. P. (Nucl. Instrum. Methods Phys. Res., Sect. B, 2010)

(untitled) - Acosta, V. M.; Bauch, E.; Ledbetter, M. P.; Santori, C.; Fu, K.-M. C.; Barclay, P. E.; Beausoleil, R. G.; Linget, H.; Roch, J. F.; Treussart, F.; Chemerisov, S.; Gawlik, W.; et al. (Phys. Rev. B, 2009)

(untitled) - Tallaire, A.; Collins, A. T.; Charles, D.; Achard, J.; Sussmann, R.; Gicquel, A.; Newton, M. E.; Edmonds, A. M.; Cruddace, R. J. (Diamond Relat. Mater., 2006)

(untitled) - Beveratos, A.; Kühn, S.; Brouri, R.; Gacoin, T.; Poizat, J.-P.; Grangier, P. (Eur. Phys. J. D, 2002)

(untitled) - Brouri, R.; Beveratos, A.; Poizat, J.-P.; Grangier, P. (Opt. Lett., 2000)

(untitled) - Hiraiwa, A.; Daicho, A.; Kurihara, S.; Yokoyama, Y.; Kawarada, H. (J. Appl. Phys., 2012)

(untitled) - Waldherr, G.; Beck, J.; Steiner, M.; Neumann, P.; Gali, A.; Frauenheim, T.; Jelezko, F.; Wrachtrup, J. (Phys. Rev. Lett., 2011)

(untitled) - Aslam, N.; Waldherr, G.; Neumann, P.; Jelezko, F.; Wrachtrup, J. (New J. Phys., 2013)